Дано:
Вектор a→ = (-4, -10, 6)
Вектор b→ = (4, -9, 2)
Вектор c→ = (8, -3, -4)
Вектор d→ = (8, 5, -8)
Найти:
1. a→ - c→
2. a→ + b→ - d→
3. a→ + b→ - c→ - d→
Решение:
1. a→ - c→:
a→ - c→ = (-4, -10, 6) - (8, -3, -4) = (-4 - 8, -10 - (-3), 6 - (-4)) = (-12, -7, 10)
Ответ:
a→ - c→ = (-12, -7, 10)
2. a→ + b→ - d→:
a→ + b→ - d→ = (-4, -10, 6) + (4, -9, 2) - (8, 5, -8) = (-4 + 4 - 8, -10 - 9 - 5, 6 + 2 + 8) = (-8, -24, 16)
Ответ:
a→ + b→ - d→ = (-8, -24, 16)
3. a→ + b→ - c→ - d→:
a→ + b→ - c→ - d→ = (-4, -10, 6) + (4, -9, 2) - (8, -3, -4) - (8, 5, -8) = (-4 + 4 - 8 - 8, -10 - 9 -(-3) - 5, 6 + 2 - 4 + 8) = (-16, -15, 12)
Ответ:
a→ + b→ - c→ - d→ = (-16, -15, 12)